PENGARUH METODE HYPNOTEACHING TERHADAP HASIL BELAJAR SISWA PADA MATERI NILAI MUTLAK - Rosmeidina Lukitasyani; Dewi Sukriyah; Risdiana Chandra Dhewy (JEDMA Jurnal Edukasi Matematika, 2022)
The teacher's role is very important because teachers can apply different procedures in the classroom to achieve their learning objectives. Today, learning with the simultaneous use of conscious and subconscious mind is widely discussed by educational professionals. Teaching with two minds is called hypnoteaching, and a teacher who practices hypnosis in the classroom is called a hypnotist. If a teacher can apply the principles of hypnosis in the classroom, then the teacher is a hypnotic teacher. This research is quantitative with the aim of knowing the effect of the hypnoteaching method on student learning outcomes. The research was conducted online at SMA Antarctica Sidoarjo class X. Determination of the sample is done randomly as many as 15 students. This study uses tests and observations as data collection techniques. Analysis of the data obtained r = 0.271 with a percentage coefficient of determination of 27.1%. Based on the partial test, it was stated that there was an effect of the hypnoteaching method on student learning outcomes in the absolute value material with a sig value. (0.046) which is more than (0.05).